Handbook of research on strategies for local e-government adoption and implementation : comparative studies - Reddick, Christopher G. (Hershey, PA : Information Science Reference, 2009)
'This book provides examinations of the adoption and impact of e-government'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Internet in public administration; Local government